Lights and shadows of the quality of democracy in Latin America - Alcántara Sáez, Manuel (2007)
A statistical study of the quality of the democracy in Latin America is made in the article, for which it is used the indices of Freedom House,IDD (Fundacion Honrad Adenauer), EIU (The Economist Intelligence Unit) and the elaborated by Levine Molina (2007), that shows asimilarity highly significant, which are stating great differences in the quality of the democracy at the countries of Latin America